Information Services: A Survey Study of College Libraries in Chandrapur District, Maharashtra - Shrikant S. Rokade; Dr. Sanjay N. Sable (International Journal of Scientific Research in Science and Technology, 2024)
The paper succinctly describes the availability of conventional and non-conventional information services in college libraries in the Chandrapur district affiliated with Gondwana University, Gadchiroli. The virtual mini survey method was adopted. Research revealed that 55% of the granted college libraries surveyed offer conventional information services, while 32% provide non-conventional information services. 30% of non-granted college libraries offer conventional information services, while 6% provide non-conventional services. The number of unaided college libraries providing information services was comparatively less. While 60% of funded college libraries had NLIST INFLIBNET membership, it was unaffordable for non-funded college libraries. The NAAC evaluation policy resulted in 70% of aided and 23% of unaided college libraries receiving support from authorities to improve information services. All 100% of computers, mobile devices, and open-access resources play a significant role in shaping information services. The Government of India has launched the “One Nation One Subscription Scheme”. Enhancing non-conventional information services is currently deemed essential.
Keywords: Information services; College libraries; INFLIBNET; NAAC; COVID-19